Evaluating study procedure training methods for a remote daily diary study of sexual minority women - Heron, Kristin E. (Mhealth, 2021)
BACKGROUND: Ecological momentary assessment (EMA) methods can be used to remotely assess physical and mental health in daily life for hard-to-reach, marginalized, and geographically dispersed populations in the U.S., such as sexual minority women (e.g., lesbian, bisexual). However, EMA studies are often complex, and engaging participants from afar can be a challenge. This study experimentally examined whether adding videos to written recruitment materials would improve consent rates, reduce dropout rates, and improve survey completion rates for an online daily diary study. METHODS: As part of a 2-week study of same-sex female couples’ health, 376 women ages 18–35 were recruited from across the U.S. using a market research firm. Couples were randomized to an introductory information condition (written + video materials or written-only materials) prior to informed consent. RESULTS: Overall, 97.1% of eligible women reviewed introductory materials and of these 96.7% consented; consent rates did not differ by condition (written + video: 97.1%, written-only: 97.1%). Dropout rates were low (5.4%) and survey completion rates were high (90.4% of surveys completed); there were no group differences for study dropout (written + video: 3.6%, written-only: 7.0%) or survey completion (written + video: 92.5%, written-only: 88.4%). Data from women randomized to receive videos indicated more than half (53.3%) did not watch any of the five videos in full. However, among those who viewed the videos, time spent watching videos, watching more videos in full, and watching at least one video in full were each positive associated with survey completion rates. CONCLUSIONS: In summary, we had high consent rates, low dropout rates, and high survey completion rates regardless of video instructions. Although sexual minority women can be hard to reach, our potential participants appeared highly motivated to take part in research, and thus video recruitment materials were not necessary to improve participation. Future experimental research to maximize EMA study design and implementation could be important for populations less inclined to participate in EMA studies, or who are less familiar with research.